(untitled) (Journal of Surgical Sciences, 2020)
Background: Haemorrhoidectomy is a surgical excision and removal of the hemorrhoid used primarily only in severe cases. There are many different types of haemorrhoidectomy like open haemorrhoidectomy and stapled haemorrhoidectomy. Objective: To compare the outcome of stapled haemorrhoidectomy and traditional open haemorrhoidectomy. Methods: This is a cross sectional study of 72 cases who underwent open and stapled haemorrhoidectomy operation for symptomatic 2nd, 3rd and 4th degree hemorrhoids. Binomial probability pre-posttest were used for statistical analysis, p value less than 0.05 was taken as significant. Results: : Among 72 patients, 34 patients of conventional haemorrhoidectomy and 38 of stapled haemorrhoidectomy at 3 months post-surgery in conventional group 1 patient was unsatisfied, 12 patients were satisfied and 4 patients stated their condition good. In stapled group 14 patients stated their condition excellent and 5 patients stated their condition good. Statistical analysis shows that level of satisfaction at 3 months post-surgery in conventional group and stapled group was statistically significant(p-value<.001). Conclusion: Stapled haemorrhoidectomy is a relatively new procedure. Stapled haemorrhoidectomy is a safe procedure, less pain and disabled than the conventional haemorrhoidectomy. Journal of Surgical Sciences (2017) Vol. 21 (2): 99-104